Instructional efficiency of integrated and separated text with animated presentations in computer-based science instruction - Kablan, Zeynel; Erden, Muenire (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
This study deals with the instructional efficiency of integrating text and animation into computer-based science instruction. The participants were 84 seventh-grade students in a private primary school in Istanbul. The efficiency of instruction was measured by mental effort and performance level of the learners. The results of the study showed that processing integrated text and animation format in computer-based science instruction requires less mental effort than the separated format, and that the performance of the students in the group with integrated presentation format group is higher than that of students in the group with separated presentation format. Instructional efficiency of the integrated presentation group was found to be higher than that of the separated presentation group. Finally, there was no difference between the two groups for instructional time. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: multimedia design; cognitive load; working memory; computer-based science instruction; COGNITIVE-LOAD APPROACH; WORKED EXAMPLES; DESIGN; ATTENTION; ARCHITECTURE; PERFORMANCE; INFORMATION; WORDS; Computer Science; Education & Educational Research